2004
DOI: 10.1074/jbc.m302637200
|View full text |Cite
|
Sign up to set email alerts
|

STAT-1 Interacts with p53 to Enhance DNA Damage-induced Apoptosis

Abstract: The STAT-1 transcription factor has been implicated as a tumor suppressor by virtue of its ability to inhibit cell growth and promoting apoptosis. However, the mechanisms by which STAT-1 mediates these effects remain unclear. Using human and mouse STAT-1-deficient cells, we show here that STAT-1 is required for optimal DNA damage-induced apoptosis. The basal level of the p53 inhibitor Mdm2 is increased in STAT-1(؊/؊) cells, suggesting that STAT-1 is a negative regulator of Mdm2 expression. Correspondingly, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
191
4
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(209 citation statements)
references
References 38 publications
9
191
4
5
Order By: Relevance
“…This is interesting since STAT-1 activation leads to antiproliferative and proapoptotic events in some cell types [38][39][40]. Likewise, islets or purified beta cells isolated from STAT1 −/− mice are resistant to IL-1β+IFN-γ-induced cell death (C. Geysemans, L. Ladriere, H. Callewaert, J. Rasschaert, D. Flamez, D. E. Levy, P. Matthys, D. L. Eizirik and C. Mathieu, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting since STAT-1 activation leads to antiproliferative and proapoptotic events in some cell types [38][39][40]. Likewise, islets or purified beta cells isolated from STAT1 −/− mice are resistant to IL-1β+IFN-γ-induced cell death (C. Geysemans, L. Ladriere, H. Callewaert, J. Rasschaert, D. Flamez, D. E. Levy, P. Matthys, D. L. Eizirik and C. Mathieu, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that inhibition of STAT1 activation blocks p53-dependent cell cycle arrest by fludarabine*, 4 and Townsend et al 3,16 showed that STAT1 and p53 cooperate together in induction of apoptosis. These results led us to raise the question of STAT1 activation by genotoxic agents.…”
Section: Resultsmentioning
confidence: 99%
“…Since STAT1 and p53 may interact with each other, 3,4 we wanted to assess the role of p53 protein in STAT1 activation by genotoxic agents. Figure 3a shows that Dx did not induce Y701-STAT1 phosphorylation in HL60 or in Jurkat cells, two p53-null cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations